ANÁLISIS DE LOS FACTORES DE RIESGOS MECÁNICOS Y SU INCIDENCIA EN LOS ACCIDENTES LABORALES EN UNA RECTIFICADORA - ORTEGA CASTILLO, JONATHAN ALEXANDER (2025)
The topic "Analysis of Mechanical Risk Factors and their Incidence in Occupational Accidents at the Palma Grinding Plant" addresses the growing concern about occupational safety in industrial environments, especially in engine rectification workshops.